CONSTRUCTING AND PROMOTING NATIONAL IDENTITY THROUGH TOURISM: A MULTIMODAL DISCOURSE ANALYSIS OF INDONESIAN OFFICIAL TOURISM WEBSITE - Sukma, Bayu Permana (Linguistik Indonesia, 2021)
This paper aims to examine the contribution of multimodal resources in the Indonesian official tourism website in constructing and promoting the Indonesian national identity. Data were gathered from 7 verbal (linguistic) texts and 13 visual (nonlinguistic) texts presented in the Indonesian official tourism website. This study draws on Wodak et al’s (2009) discursive strategies of national identity construction and Kress and van Leuween’s (2006) theory of visual design. The results of the study show that the combination of verbal and visual texts in the Indonesian official tourism website contribute to the Indonesian national identity construction and promotion. The constructed and promoted Indonesian national identities are 1) Indonesia as a country with the rich natural landscape; 2) Indonesia as an archipelagic tropical country; 3) Indonesia as a maritime country; 4) Indonesia as a technologically advanced country; 5) Indonesia as a modern country; 6) Indonesia as a multicultural country; 7) Indonesia as a country with cultural richness; 8) Indonesians as people who are open to strangers or foreigners; 9) Indonesians as kind and friendly people; and 10) Indonesians as modern people.